2021
DOI: 10.3390/computation9050054
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multi-Model Face Shape and Eye Attributes Identification for Hair Style and Eyelashes Recommendation

Abstract: Identifying human face shape and eye attributes is the first and most vital process before applying for the right hairstyle and eyelashes extension. The aim of this research work includes the development of a decision support program to constitute an aid system that analyses eye and face features automatically based on the image taken from a user. The system suggests a suitable recommendation of eyelashes type and hairstyle based on the automatic reported users’ eye and face features. To achieve the aim, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Alzahrani et al [14] presented a recommendation model that recognizes gender, face type and eyebrow type from an input face image. Their model recommends hairstyles and eyelash styles for women and hair styles for men by combining the recognized information.…”
Section: Anthropometrical Facial Feature-based Deep Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzahrani et al [14] presented a recommendation model that recognizes gender, face type and eyebrow type from an input face image. Their model recommends hairstyles and eyelash styles for women and hair styles for men by combining the recognized information.…”
Section: Anthropometrical Facial Feature-based Deep Learning Modelsmentioning
confidence: 99%
“…To provide a quantitative measurement of a facial impression, we conducted a comprehensive review of anthropometry studies [4,6,7,[9][10][11][12][13][14][15]18,19,23,25,28] and collected 68 facial features, eliminating any duplicates. These features are suggested in Appendix A.…”
Section: Definition Of An Xfofmentioning
confidence: 99%
“…An efficient method for detecting eye contours was proposed in realtime with the dataset of the eye contours [7]. For shape classification of eyes, Alzahrani et al summarized the characteristics of eye shapes and designed eye shape classification rules [3]. In this work, we originally design the classification rules by collecting relevant information and confirm the effectiveness of our classification rules by conducting evaluation study.…”
Section: Eye Featuresmentioning
confidence: 99%
“…We reviewed different typical eye types, such as round eyes: larger and more circular; close-set eyes: less space between eyes; down-turned eyes: taper downward at the outer corner [3]. We found that the eye shapes are related to the size of the eye, the angle of the eye outer corner, and the distance between the two eyes.…”
Section: Eye Features Analysismentioning
confidence: 99%
“…With advancements in machine learning and computer vision techniques, deep neural network models are becoming very successful and widespread. Considering that deep learning architectures have been successfully used in various fields, including facial image analysis [16][17][18], it could even further be exploited to detect the faces disguised by makeup to overcome the flaws in many facial-related analysis methods. Those models have the ability to extract the features directly from images without the need for human interaction by training on large datasets using various types of learning schemes.…”
Section: Introductionmentioning
confidence: 99%